2018
DOI: 10.1177/0956462418775524
|View full text |Cite
|
Sign up to set email alerts
|

Partner meeting venue typology and sexual risk behaviors among French men who have sex with men

Abstract: Previous research has given considerable attention to venues where men who have sex with men (MSM) meet their sex partners. However, no previous study examined a vast range of sexual risk behaviors. The objective of this study was to examine the association between the types of venues for meeting sexual partners, condomless anal intercourse, engagement in group sex, and HIV and sexually transmitted infection (STI) risk among a sample of MSM. Users of a popular geosocial-networking app in Paris were provided an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…First, these venues may influence the probability of meeting partners with certain risk characteristics 5. Second, the situational conditions found at different venues for social interaction may influence the social acceptability of risky behaviours such as excess alcohol use, having sex with a new or casual partner, condom use and anal sex, hence increasing HIV or sexually transmitted infection (STI) transmission 1 6 7. A number of studies across different countries have found sexual risk-taking among workers and customers at venues for social interaction 8–11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, these venues may influence the probability of meeting partners with certain risk characteristics 5. Second, the situational conditions found at different venues for social interaction may influence the social acceptability of risky behaviours such as excess alcohol use, having sex with a new or casual partner, condom use and anal sex, hence increasing HIV or sexually transmitted infection (STI) transmission 1 6 7. A number of studies across different countries have found sexual risk-taking among workers and customers at venues for social interaction 8–11.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research, both qualitative and quantitative, has given considerable attention to venues where people meet sexual partners. Studies, including some in Africa, have mapped and characterised these venues,4 26–29 while others have examined sexual behaviours and HIV seroprevalence of workers and customers at venues for social interaction 2 6 8 11 12. Relatedly, other studies have assessed availability of HIV preventive interventions at venues for social interaction and provided a case for support for venue-based HIV programmes 2 30–32.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of sexual venues and other locales frequented by MSM in developed countries suggest socioenvironmental factors are associated with sexual risk-taking, highlighting the particularly high-risk intercourse at commercial sex venues [59]. Factors associated with attending sex venues include reporting a high number of male sexual partners, sex while on methamphetamine and/or marijuana, group sex, and CAI with a partner whose HIV status was unknown [5, 10, 11]. While few studies out of lower-middle income countries have addressed correlations between CAI and location where sex occurred, a 2017 study in Tijuana, Mexico found higher levels of CAI were associated with more frequent contacts with sexual partners at public venues in the last 2 months [12].…”
Section: Introductionmentioning
confidence: 99%